Performance body and measurements of yaks and their hybrids under field condition - RAMESHA, K P; KATAKTALWARE, M A; DAS, SANDEEP; POUROUCHOTTAMANE, R; BANDOPADYAYA, S; SARAVANAN, B C; KRISHNAN, G; SARKAR, M; BHATIACHARYA, M (The Indian Journal of Animal Sciences, 2011)
Performance and body measurements of yaks and their hybrids under field conditions have been studied. Body measurements, inter-calving period and productive performance of yaks and their hybrids were estimated. The female hybrids were fertile and produced higher milk than both parents but male hybrids were sterile. Â